(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the factors associated with the selection of surgical methods for uterine fibroids. Methods: A cross-sectional descriptive study using convenience sampling was conducted on 590 patients diagnosed with uterine fibroids who had indications for surgery at Nghe An General Friendship Hospital from January 1, 2024, to December 31, 2024. Results: The myomectomy group had the lowest mean age (41.15 ± 6.37 years old) and predominantly consisted of patients under 45 years of age (85.4%). In the postmenopausal group, 100% of patients underwent total hysterectomy. In the premenopausal group, myomectomy and subtotal hysterectomy accounted for 15.8% and 14.6%, respectively. Patients with a single tumor were most frequently indicated for total hysterectomy (66.9%), followed by myomectomy (19.1%) and subtotal hysterectomy (14%). For tumors smaller than 5 cm, the rate of myomectomy was high (26.8%). When tumor size increased to 5-10 cm, the myomectomy rate decreased to 12.7%, and total hysterectomy became the primary choice (77.7%). Patients with tumors in locations L0-2 and L6-7 were indicated for myomectomy at higher rates (50% and 66.7%, respectively) compared to those with tumors in locations L3-5 (13.6%); the reverse trend was observed for total hysterectomy. Conclusion: The choice of surgical method is closely dependent on age, fertility desire, menstrual status, tumor size, and the number of tumors. Myomectomy is prioritized for young women with a desire for fertility preservation, whereas total hysterectomy is indicated for older patients, postmenopausal women, or those with large tumors.